A Study on Postpartum Depression in Tertiary Care Hospital: Implication for Maternal Mental Health - Jagdale, Supriya; Dengi, Aishwarya; Datar, Meghana; Sunil, Lakshmi; Sudev, Krishna R.; Garg, Pooja (International Journal of Statistics in Medical Research, 2026)
Background: Postpartum depression (PPD) is a significant maternal health issue often overlooked in India. This study assesses its prevalence, risk factors, and implications in a tertiary care hospital in Pune. Methods: A cross-sectional study was conducted from March 2025 to June 2025, involving 102 postpartum women. The Edinburgh Postnatal Depression Scale (EPDS) was used to assess depression immediately postpartum and at six months Results: The incidence of PPD was 12.75% immediately postpartum and 15.69% at six months. Significant risk factors included young maternal age (<20 years), low family income, unplanned pregnancy, preterm birth, antenatal complications, and low self-esteem. Employment status and lack of antenatal care were also associated with higher EPDS scores. However, factors such as education level, delivery mode, and baby’s gender did not show statistical significance. Conclusion: PPD is a prevalent yet underdiagnosed condition that requires urgent integration into maternal healthcare programs. Early screening, mental health support, and targeted interventions can improve outcomes for mothers and infants. Further research and policy focus on maternal mental health are necessary for better healthcare delivery.